Auto/ethnography: a pathway to share the story - McCarthy, Helen C.D. (Common Ground, 2016)
As a teacher for more than thirty years, I have learned from the Warnumamalya, Yolngu, Nyungar, and Wongi peoples of Australia, and observed Indigenous parents and teachers often express dissatisfaction with the way mainstream non-Indigenous education is delivered in their community schools. I understood as a non-Indigenous teacher I did not have a right to speak for Indigenous parents but saying nothing about the anglo-centric educational focus made me feel culpable, leaving me suspended in the rancor of my own silence. How could I express the unease I felt without being another “know-it-all” non-Indigenous teacher writing about Indigenous students experiences? Respecting that it was not my place to write about or for the other, I chose to write my story using the interpretive research design auto/ethnography as a referent within an interpretive paradigm. Auto/ethnography ensures the writing process and the writing product are deeply personal and political, delivering the necessary multidimensionality to enmesh emerging personal/professional themes. This methodology provided a pathway to venerate my experiences as a white teacher living and learning in black communities, where I came to understand the attendant epistemologies within both cultural interfaces. While the product of my research/the struggle to establish culturally sensitive educational pathways for students is vital, the focus of this paper relates specifically to the personal processes involved in using “story telling” as an authentic data source to best illuminate the inquiry.